Students' academic performance application guideline / Norshuhada Samsudin ... [et al.] - Samsudin, Norshuhada; Syed Abdullah, Sharifah Sarimah; Ahmad Shukri, Fuziatul Norsyiha; Wan Mohd Rosly, Wan Nur Shaziayani; Omar, Mawardi (Unit Penerbitan JSKM, 2022)
Every educational institution has educators who participate in the recording of assessment results for students. This is to make sure that educators can continue to be held accountable for the confidential results of their students. Academic performance indicators, such as marks and grades, offer details about students' development and help educators to decide what kind of instruction their students will require. This study developed the Students' Academic Performance Application to track assessment outcomes simply for students. Hence, to construct this system, data studio application software was employed. Additionally, it can make it easy for educators to monitor students' growth and progress, as well as any weak areas. A great technique to precisely track each student's improvement is to create a special folder for them. Each folder can be used to store documents that serve as evidence of the students' academic achievement.